Barack Obama, Civil Mourning, and Prudence in Presidential Rhetoric. Issue 2 (3rd April 2017) - Perry, Samuel
ABSTRACT: This essay analyzes Barack Obama's response to the death of Trayvon Martin and acquittal of George Zimmerman. It compares Obama's response to previous instances of presidential rhetoric concerning racial violence during the long history of the civil rights movement prescribed by Jacqueline Dowd Hall. Obama shifts notions of prudence in presidential rhetoric in this address by directly attending to the protests surrounding the verdict in the Zimmerman trial and by publicly mourning Trayvon Martin. The dialogue between Obama and protestors constitutes a form of civil mourning, which keeps open the possibility for conversations about race and racism. While Obama does not offer major policy solutions or push for federal intervention in the case, his remarks set up a framework of civil mourning that allowed his administration to continue to address civil rights protests differently than his many of predecessors.